The Importance of Implementing Formative Evaluation in Islamic Education Learning - Siti Halimah; Shonia Tita Amelina; Vernisa Okta Ramadhani; Nisyyah Khoirotul Ilmiah (Universitas Islam Lamongan, 2026)
This research aims to explain the implementation of formative evaluation in Islamic Religious Education (IRE), identify the challenges teachers face during its application, and describe the follow-up actions taken to improve the effectiveness of teaching and learning. Using a qualitative approach through a literature review method. Through formative assessment, teachers are able to monitor students’ learning progress, identify difficulties, and adjust instructional strategies to better suit learners’ needs. The results also indicate that formative evaluation encourages greater student engagement, strengthens learning motivation, and enhances the overall learning process in IRE classrooms. Furthermore, formative evaluation provides a solid basis for implementing remedial programs for students who experience difficulties and enrichment activities for those who have mastered the material. This reserach concludes that formative evaluation is an effective instrument for improving educational quality while simultaneously fostering meaningful character formation in Islamic Religious Education.